The Epidemiology of Sepsis in Childhood. (January 2017) - de Souza, Daniela Carla; Barreira, Eliane Roseli; Faria, Lucília Santana
ABSTRACT: Background: Sepsis, or systemic inflammatory response to infection, is a major childhood disease and a common cause of death in children. Despite its importance, a global perspective on the epidemiology and mortality of pediatric sepsis across the world is still lacking. Methods: A non-systematic review of the medical articles published in Medline from 2005 to 2015. Results: Studies suggest that there has been a rise in the number of pediatric sepsis cases along the last two decades, which may relate to the increased survival of preterm and low birth-weight infants and children with severe chronic conditions. Children living in low-income countries represent a vulnerable population for sepsis. Despite several initiatives to improve the diagnosis and early treatment of pediatric sepsis, the mortality resulting from pediatric sepsis remains high, ranging from 5% to 40%. Poor outcomes, however, do not seem to be related to the limitation of resources but to the delay in the recognition and early treatment of sepsis. Conclusions: Educational efforts aiming to increase the awareness on sepsis by the general public and the adherence to the treatment guidelines by healthcare providers may result in significant improvements in sepsis survival. The global attention to pediatric sepsis, however, can only be achieved with the standardization of the definitions and the use of simple and sensitive diagnostic criteria that incorporate the differences in the necessities among different settings and the availability of local resources.